QUESTION MORAL QUALITIES THROUGH MATHEMATICS IN THE LANGUAGE AND LITERACY TEXTBOOK - Tursunmatova Bakhtiniso Boshbekovna (Journals Park Publishing, 2023)
This article questions moral qualities through the textbooks in the language and literacy textbook. Language and literacy classes include developing accurate, fast, intelligent expression skills for a student, expanding knowledge of the environment by elevating them from a simple book reader to a deeply distinguyed creative bookmaker, enriching their worldview by reading and understanding texts of any style, and acquiring critical creative thinking skills. The main task of primary school language and reading lessons is to prepare students for their academic activities, to form a person who can communicate with others and express themselves to others in an understandable way.
Keywords: speech, speech culture, elementary school, students, methodology, native language reading literacy